1996
DOI: 10.1902/jop.1996.67.7.694
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Microbial Colonization of Barrier Membranes for Guided Tissue Regeneration

Abstract: The microbial colonization of expanded polytetrafluoroethylene membrane by putative periodontopathogens at 3 minutes of intraoral manipulation was determined in 42 patients with 42 mandibular posterior two‐ to three‐wall defects. Twenty patients exhibited no periodontal pockets of ≥ 5 mm, other than the study site, and low levels of pathogens (group A). Twenty‐two patients revealed multiple periodontal pockets of 5 mm or more and numerous pathogens (group B). Within the preceding 3 months of regenerative surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 29 publications
1
93
0
1
Order By: Relevance
“…[25][26][27] Microbial colonization of the membranes in GTR studies can deleteriously affect the newly formed cells and decrease the amount of regenerative healing. 32 Membrane exposure has also been in association with gingival recession. 33 In this study however, we did not observe any exposure of the membranes to the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] Microbial colonization of the membranes in GTR studies can deleteriously affect the newly formed cells and decrease the amount of regenerative healing. 32 Membrane exposure has also been in association with gingival recession. 33 In this study however, we did not observe any exposure of the membranes to the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…However, collagen membranes seem to disintegrate at a high rate when exposed to the oral environment 40 owing to collagenases produced by several oral bacteria, including Porphyromonas gingivalis and Bacteroides melaninogenicus. 41,42 Consequently, some authors advise the use of multiple layers of collagen in cases where primary closure is not achievable or secondary exposure of the membrane is likely to occur. 43 On the defect side of a GTR-treated defect, the population of the membrane's surface with cells promoting regeneration is desirable.…”
Section: Cells Used For In Vitro Studiesmentioning
confidence: 99%
“…While osteoblasts were found in only one of the two compartments, fi broblasts could be found on both sides of the membrane (only in GTR). In a series of animal studies, Karring et al were able to show that PDL fi broblasts are able to initiate periodontal regeneration, while this capacity is not found in gingival fi broblasts or bone cells [31][32][33][34][35][36][37][38][39][40][41][42][43][44] (for a review see Karring et al 34 ). Therefore, studies using PDL fi broblasts are reviewed separately at the end of this section.…”
Section: Behavior Of Fi Broblasts On Collagen Membranesmentioning
confidence: 99%
“…Barrier membranes are at risk of becoming contaminated within 3 min of intraoral membrane manipulation in individuals with multiple deep periodontal pockets, bleeding on probing in other parts of the dentition, and high subgingival levels of putative periodontopathogens. Research has shown a negative correlation between bacterial contamination of the membrane and clinical attachment gain (25).…”
Section: Patient Factors Influencing Successful Regenerationmentioning
confidence: 99%